Five stages of planning for the proposed training aspects of football - Nagi, Deyaa (Journal of Physical Education, 2015)
Sports training planning football his impact actor in the achievement relies most advanced countries depending planning altogether and research problem is concentrated in the neglect of creating an easy and simple way to plan sports training football through the most established training courses in Iraq, prompting the researcher to put five proposed help stages trainers in the training aspects Pkrhkaddm planning process. It was explained these stages on a sample of the instructors participating training course Asian (B) and then distributed them to show how the proposed stages and the extent of their learning her questionnaires and a week later was withdrawn questionnaires after filling by the sample and the objective of this research is to develop phases of planning training training aspects football and the imposition of the proposed research focuses on five stages help coaches in planning training curricula football and Ba Find out conclusions, including that the proposed five stages have reported slice coaches in planning training aspects of football who were part of the research sample